Gastrintestinal helminths Of Cerdocyon thous (Linnaeus, 1766-Smith, 1839) from the caatinga area of the Paraiba State, Brazil - Lima, Roberto Cesar [UNESP]; Lux Hoppe, Estevam Guilherme [UNESP]; Tebaldi, Jose Henrique [UNESP]; Cruz, Breno Cayeiro [UNESP]; Barros Gomes, Alberio Antonio [UNESP]; Nascimento, Adjair Antonio [UNESP] (Universidade Estadual de Londrina (UEL), 2013)
The crab eating fox, Cerdocyon thous (Linnaeus, 1766 - Smith, 1839), is a medium sized canid which is found in almost every region of Brazil. It is the only registered native canid specie to be found in the semi-arid Northeastern region of the country. This study had as its objectives: the identification of the helminth fauna common to Cerdocyon thous found in the Caatinga of the state of Paraiba; and the determination of the ecological indications of helminthic infection, hoping to make a favourable addition to the understanding of this little known biome. In this study, 58 animals that were found as 'roadkill' on the highways in the municipality of Patos were used. The gastrointestinal helminths from these animals were colected. All the animals in this study were infected with helminths. 16 species of helminths were identified, two being trematodes, one being a cestode, one being an acanthocephalus, and the remaining twelve being nematodes. In this study a new specie, named Pterygodermatites pluripectinata n. sp. was discovered and its host and location described.
Keywords: Caatinga; Cerdocyon thous; Helminthfauna; Ecological descriptors